Mediating effects of perceived organisational support on organisational justice and commitment relationship among Malaysian school sports volunteer coaches - Ooi, Cheng Lee (2016)
Little is known on how perceived organisational support as an exchange mechanism could explain the inconsistent findings between organisational justice and organisational commitment, particularly among public school sports volunteer coaches. This study is the first to examine whether perceived organisational support mediates the relationships between the four-dimensional organisational justice and the threecomponent organisational commitment of the Malaysian High Performance School Sports Developmental Programme (SPTS) volunteer coaches, in an organisationsponsored volunteerism at grass root sports development level. A cross-sectional correlation research mail survey was conducted. Data from 750 respondents were analysed by using IBM SPSS statistics software and structural equation modeling with AMOS. Findings showed that interpersonal justice related positively with affective commitment but negatively with continuance commitment; while, distributive justice was only linked to normative commitment. All four dimensions of organisational justice except procedural justice were associated with perceived organisational support. Perceived organisational support relates only to normative commitment. Findings also showed that perceived organisational support mediated distributive justice and informational justice on continuance commitment, and together with interpersonal justice on normative commitment. However, no mediation of perceived organisational support was found on all four dimensions of organisational justice with affective commitment. In conclusion, perceived organisational support has made the fairness process more definitive in explaining these Malaysian SPTS volunteer coaches’ organisational commitment. This study implied that Malaysian SPTS volunteer coaches have high normative commitment, but are not impressed from their perception of procedural justice due to Malaysian culture of collectivism, hierarchical organisation structure and high power distance. Moreover Organisation Support Theory, under current research, is suggested to contextualise and resolve their conflicting dual roles as a teacher by contract and as a volunteer coach by assignment within the organisation. Besides, it is essential to strengthen the Sports Officers’ capabilities and abilities in volunteer sports management in order to achieve Malaysia’s aim for sports excellence. Future in-depth research is recommended for a better understanding of the subject matter.